Dis-Place Theologizing: Fragments of Intercultural Adventurous God-Talk - Jagessar, Michael N. (Black theology, 2015)
A danger for all Black contextual/liberative theologians is that of unconsciously somersaulting into homogenizing and static tendencies about Black experiences and contexts. So while we (Black and Asian theologians) argue for cultural agency before dominant White audiences and in the company of our own punters, is it not possible that we become complicit in the cause of levelling our intra-cultural dynamics as we ignore our own cultural biases and often un-deconstructed inherited traditions? If Black theology (or any liberative form of God-talk) is about embodying change and transformation, this article suggests that intercultural conversations, with necessary caveats, are a necessary undertaking. What will an intercultural vocation in Black liberating God-talk look like? Can such a multi-faceted habit/method through creolized spaces of (inter)action/being open up new vistas for constructive dialogue with, between and among theological perspectives and towards a more holistic model of transformation?